U-ABC : Schilderijen, Beelden, Fotografie uit Uruguay, Argentinië, Brazilië, Chili. - Amaral, Aracy; Barents, Els; Beeren, W.A.L.; Kalenberg, Angel; Mignot, Dorine; Whitelow, Guillermo; Zurita, Raul (Amsterdam : Stedelijk Museum Amsterdam, 1989)
Andujar, Claudia ; Benedit, Luis Fernando ; Berredo, Hilton ; Bertoni, Claudio ; Rio Branco, Miguel ; Catunda, Leda ; Crescenti, Leonardo ; Dominguez, Pablo ; Errázuriz, Paz ; Espínola Gómez, Manuel ; Kuitca, Guillermo ; Mariani, Anna ; Nakle, Gustavo ; Nassar, Emmanuel ; Nuñez, Francisca ; Pintor, Oscar Diego ; Salgado, Sebastião ; Schvartz, Marcia ; Senise, Daniel ; Stolkiner, Raúl Eduardo ; Tunga ; Varejao, Adriana ; Vasconcellos, Cássio
biog., ind. tent., gr. tent. p. 130-134, bibliog. p. 135
U-ABC : Schilderijen, Beelden, Fotografie uit Uruguay, Argentinië, Brazilië, Chili, Stedelijk Museum Amsterdam, 23.09.1989 - 12.11.1989
Nederlands & Engels
boek
Keywords: Argentinië; Brazilië; Chili; Uruguay